Role of Bin‐Amphiphysin‐Rvs (BAR) domain proteins in mediating neuronal signaling and disease. Issue 11 (29th July 2022) - Mallik, Bhagaban; Bhat, Sajad; Kumar, Vimlesh
Abstract: Several proteins contain signaling domains that can regulate the cell membrane dynamics as well as the underlying cytoskeleton. Among these, Bin‐Amphiphysin‐Rvs (BAR) domain‐containing proteins, with their membrane deforming properties, have emerged as the key players in regulating neuronal morphology and inducing neuronal signaling that can modulate synaptic architecture. While the biochemical and structural basis of membrane deformation by the BAR‐domain proteins has been extensively studied, the in vivo contexts in which these proteins function remain to be elucidated. Despite the discovery of BAR‐domain proteins over 25 years ago, most of the studies have primarily focused on understanding the structural and biochemical properties and cell biological processes regulated by these proteins. Understanding the functional requirements of these proteins at the level of multicellular organisms and the way these proteins regulate biological processes remains a topic of intensive study. In this review, we discuss the functional roles of BAR‐domain proteins in the context of membrane dynamics and cellular signaling. We highlight recent developments describing the functional role of these proteins in neuronal morphogenesis, synaptic function, and disease. Graphical Abstract: This figure shows regulation of numerous functions by the BAR‐domain containing proteins in the cells. In association with other signaling motifs, the BAR domain induces membrane curvature by rearranging the underlying membrane cytoskeleton. Rearrangement of the membrane cytoskeleton is one of the critical processes during synapse growth. Due to its membrane deforming activity, BAR‐domain containing proteins can act as signaling molecules for clustering various synaptic molecules at the membrane. Besides, the amphipathic helix of the BAR domain can be directly inserted into the membrane and induces the formation of synaptic vesicles or endosome‐like structures in neurons.